DEMIURGY IN THE WORKS OF PELEVIN (Eureka Journal of Language, Culture & Social Change, 2026)
V. Pelevin's novel "T" was published in the fall of 2009, and its resonance continues to this day – both in blogs and in the media. This article examines the phenomenon of demiurgy in the works of Viktor Olegovich Pelevin as a key principle for organizing artistic reality. The philosophical, mythological, and postmodern foundations of the writer's demiurgic thinking are analyzed, as well as its connection to issues of simulation, power, subjectivity, and language. Particular attention is paid to the image of the author-demiurge, the demiurge characters, and the reader as a participant in the construction of meaning.
Keywords: A. Schopenhauer, V. Pelevin, demiurgy, literary criticism, artistic reality, novel “T”, postmodernism, classification, philosophy, Russian literature.